2020
DOI: 10.3390/toxins12060387
|View full text |Cite
|
Sign up to set email alerts
|

The Synergism of PGN, LTA and LPS in Inducing Transcriptome Changes, Inflammatory Responses and a Decrease in Lactation as Well as the Associated Epigenetic Mechanisms in Bovine Mammary Epithelial Cells

Abstract: Mastitis is usually caused by a variety of pathogenic bacteria that include both Gram-positive and Gram-negative bacteria. Lipopolysaccharide (LPS) is the pathogen-associated molecular pattern (PAMP) of Gram-negative bacteria, and peptidoglycan (PGN) and lipoteichoic acid (LTA) are those of Gram-positive bacteria. The effects of LPS, PGN and/or LTA on inflammatory response and lactation in bovine mammary epithelial cells (BMECs) are well studied, but the epigenetic mechanisms of their effects received less att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The expression of cytokines displayed an overall increase, when LPS concentration was raised to 0.1 μg/mL. In our previous study, 0.1 μg/mL LPS induced an overall increase in the expression of cytokines [ 43 ] and caused hypomethylation of genes involved in the immune pathways [ 44 ], which successfully promoted inflammatory responses of BMECs. In a study by Guenther et al [ 38 ], they found that 0.1 μg/mL LPS enhanced the expression of inflammatory factors, including IL-8 and C-C motif chemokine ( CCL ) 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of cytokines displayed an overall increase, when LPS concentration was raised to 0.1 μg/mL. In our previous study, 0.1 μg/mL LPS induced an overall increase in the expression of cytokines [ 43 ] and caused hypomethylation of genes involved in the immune pathways [ 44 ], which successfully promoted inflammatory responses of BMECs. In a study by Guenther et al [ 38 ], they found that 0.1 μg/mL LPS enhanced the expression of inflammatory factors, including IL-8 and C-C motif chemokine ( CCL ) 5 .…”
Section: Discussionmentioning
confidence: 99%
“…LPS, PGN and LTA are PAMPs [ 5 , 6 ]. All of them can act as antigens and will induce an inflammatory response if present in the peripheral blood, resulting in injury to the body cells and tissues [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…LPS, PGN and LTA are PAMPs [ 5 , 6 ]. All of them can act as antigens and will induce an inflammatory response if present in the peripheral blood, resulting in injury to the body cells and tissues [ 5 , 6 ]. High concentration of LPS induced by HC diet usually results in ruminal epithelium injury, such as inflammation [ 42 ], apoptosis, high osmolarity [ 43 ], etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation was reported to regulate the expression of IL-6R rather than genetic mutations in response to mastitic pathogen ( Zhang et al, 2018a ). Moreover, the co-stimulation of bovine mammary epithelial cells with LPS, peptidoglycan (PGN), and lipoteichoic acid (LTA) significantly increased DNA hypomethylation compared with LPS stimulation, indicating that the additive effects of co-stimulation decreased methylation levels resulting in increased transcriptome changes and inflammatory responses ( Wu et al, 2020c ). The hypermethylation of the CD4 promoter was reported to repress its gene expression in Holstein cows with clinical mastitis ( Wang et al, 2013 ; Usman et al, 2016 ).…”
Section: Evidence Of the Impacts Of Epigenetic Processes On Livestockmentioning
confidence: 99%